STOP HPV study protocol: a nationwide case–control study of the association between oropharyngeal cancer and human papillomavirus (HPV) infection in Brazil - Juliana Comerlato; Marina Bessel; Natalia Luiza Kops; Jaqueline Driemeyer Correia Horvath; Flávia Moreno Alves de Souza; Gerson Fernando Mendes Pereira; Eliana Marcia Wendland; Daniel Sperb; Cristina Pimenta; Frederico Soares Falcetta (BMJ Open)
Introduction Human papillomavirus (HPV) is the most common sexually transmitted infection and is associated with several types of cancer. The number of cases of HPV-associated head and neck squamous cell carcinomas (HNSCCs), especially oropharyngeal carcinomas, has increased significantly in recent years despite decreased tobacco smoking rates. Currently, no data concerning the risk factors and prevalence of HPV in HNSCC patients in all regions of Brazil are available, making it difficult to promote advances in this field of public health. Therefore, our goal is to determine the impact of infection by HPV, including HPVs with different genotypes, on head and neck cancer and the risk factors associated with the development of head and neck cancer in all regions of Brazil.Methods and analysis This is a case–control study that will include 622 patients and 622 controls from all regions of Brazil. A questionnaire will be applied to gather information on sociodemographic, behavioural and health factors. Oral, cervical or penile/scrotal, and anal specimens and serum samples will be collected from all participants. Formalin-fixed paraffin-embedded tissue from tumour biopsies will be analysed only in the case group. Molecular and serological analyses will be performed to evaluate the presence and role of HPV in the development of head and neck cancer.Ethics and dissemination This project was approved by the research ethical committee of the proposing institution (Hospital Moinhos de Vento, number 2.852.060). Ethical approval from the collaborators is currently under evaluation and is not yet complete. The results of this study will be presented at meetings with the Brazilian Ministry of Health through technical reports and to the scientific community at national and international events, with subsequent publication of scientific articles.